2015
DOI: 10.1016/j.bbi.2014.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced modulation of NF-κB activation, inflammation-associated gene expression, and cytokine levels in blood of healthy men

Abstract: Acute psychosocial stress stimulates transient increases in circulating pro-inflammatory plasma cytokines, but little is known about stress effects on anti-inflammatory cytokines or underlying mechanisms. We investigated the stress kinetics and interrelations of pro- and anti-inflammatory measures on the transcriptional and protein level. Forty-five healthy men were randomly assigned to either a stress or control group. While the stress group underwent an acute psychosocial stress task, the second group partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…Heart; blood Stress duration dependent " plasma CORT; ; heart histamine level; " serum histamine level; " mast cell degranulation Huang et al " plaque size; " hematopoietic system activity; " plaque protease levels; " intimal neutrophils, monocytes and macrophages; " necrotic core area; ; fibrous cap thickness; " plaque monocyte inflammatory gene expression No significant difference in bodyweight; total cholesterol Dutta et al (2012) Similar to the response to chronic stress, acute stress exposure has been demonstrated to result in a quick rise in plasma interleukins and inflammatory markers (Table 1) (Yamauchi et al, 2013;Wilbert-Lampen et al, 2010;Schultze-Florey et al, 2012;Cohen et al, 2015;Suarez, 2004;Coccaro et al, 2014;Slavish et al, 2015), such as IL-6, IL-1b and sICAM (Heinz et al, 2003;Kuebler et al, 2015), which have all been demonstrated to be proatherogenic. Furthermore, the rise in plasma IL-6 was seen to associate with fibrin formation and pro-coagulant markers (von Känel et al, 2005), which may lead to an enhanced risk of thrombosis upon plaque rupture.…”
Section: Acute Stress and Acute Cardiovascular Syndromesmentioning
confidence: 97%
“…Heart; blood Stress duration dependent " plasma CORT; ; heart histamine level; " serum histamine level; " mast cell degranulation Huang et al " plaque size; " hematopoietic system activity; " plaque protease levels; " intimal neutrophils, monocytes and macrophages; " necrotic core area; ; fibrous cap thickness; " plaque monocyte inflammatory gene expression No significant difference in bodyweight; total cholesterol Dutta et al (2012) Similar to the response to chronic stress, acute stress exposure has been demonstrated to result in a quick rise in plasma interleukins and inflammatory markers (Table 1) (Yamauchi et al, 2013;Wilbert-Lampen et al, 2010;Schultze-Florey et al, 2012;Cohen et al, 2015;Suarez, 2004;Coccaro et al, 2014;Slavish et al, 2015), such as IL-6, IL-1b and sICAM (Heinz et al, 2003;Kuebler et al, 2015), which have all been demonstrated to be proatherogenic. Furthermore, the rise in plasma IL-6 was seen to associate with fibrin formation and pro-coagulant markers (von Känel et al, 2005), which may lead to an enhanced risk of thrombosis upon plaque rupture.…”
Section: Acute Stress and Acute Cardiovascular Syndromesmentioning
confidence: 97%
“…Evidence shows that the binding activity of the nuclear factor-kappaB (NF-kB), a key mediator of inducible transcription in the immune system and inflammatory genes, is enhanced by exposure to acute stress in humans. This is likely mediated through adrenergic receptor stimulation [4,6,7] and appears to be inversely related to glucocorticoid responses [7,8].…”
mentioning
confidence: 99%
“…Both acute and chronic psychosocial stress have been associated with the release of proinflammatory cytokines, e.g., TNF-α and IL-6 [12][13][14][15] , and, as mentioned above, pain and acute psychological distress are correlated during AMI.…”
Section: Introductionmentioning
confidence: 99%